Effects of round bale feeding sites on soil fecal bacteria and nutrient concentrations - Lenehan, N.A.; Marston, T.T.; Christian, Michael L.; Marchin, G.L.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted over seven months (January to July 2003) to evaluate fecal bacteria and nutrient concentrations in soil surrounding round bale feeders at winter feeding sites. Six-inch soil samples were taken each month from a total of ten feeding sites, at distances of 10, 40, 70, and 100 feet from each feeder. Soil samples were taken before (January) livestock access to the sites, during (February, March, and April) the feeding period, and after (May, June, and July) cattle had been removed from the sites. Results indicate that fecal bacteria concentrations increased over the duration of feeding period and were greatest at close proximity to round bale feeders. The data suggest that environmental contamination due to fecal bacteria in the soil can occur up to 100 feet from the feeding site. For soil nutrients, the greatest increase generally occurred at 10 feet from the feeders, with few differences thereafter.
Keywords: Beef; Round bales; soil fecal bacteria; Nutrient concentrations